PEMBINAAN ORGANISASI PERANGKAT DAERAH TERHADAP BADAN USAHA MILIK DESA DI KECAMATAN SINGINGI HILIR TAHUN 2020-2021 - Azlan Ramadhan; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The number of BUMDes with basic classification in Riau Province, especially in Kuantan Singingi Regency, is 165 BUMDes with basic classification or 70 percent of the total 218 BUMDes in Kuantan Singingi Regency. BUMDes with this basic classification are BUMDes that accumulatively are BUMDes with a low level of development classification that have management and management quality that is below the assessment standard such as poor capital management capabilities, poor governance and management or those that do not yet have work programs and arrangements. institutions or organizations that are not yet good as well as financial books that do not yet exist or that are experiencing stagnation in management. Singingi Hilir Subdistrict was taken to see the coaching efforts carried out by the Regional Apparatus Organization because Singingi Hilir Subdistrict is a sub-district in Kuantan Singingi Regency which has various variations of the BUMDes classification, so it is very interesting to study, namely to see the implementation of coaching carried out by the Regional Apparatus Organization, namely the Empowerment Service Communities and Villages of Riau Province, Community and Village Empowerment Office of Kuantan Singingi Regency, and District Government, namely the government of Singingi downstream district. This study aims to determine the implementation of coaching carried out by Regional Apparatus Organizations for Village-Owned Enterprises in Singingi Hilir District. This study uses the concept of coaching santoso from four indicators, namely guidance, provision of platforms, education and training, and supervision of field visits. This study uses a qualitative descriptive method and data collection techniques based on observation, literature study and interviews. The results of this study indicate that there is still a lack of guidance for BUMDes in Kuantan Singingi Regency carried out by regional apparatus organizations and even from each regional apparatus organization there is still no visible coaching program that is directly visible apart from the sub-district apparatus, namely the Singingi downstream sub-district government in the Subdistrict Singingi Hilir. Keywords: Development of BUMDes, Regional Apparatus Organizations